2017
DOI: 10.1093/nar/gkx1208
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of 53BP1 dictates the DNA double strand break repair pathway

Abstract: P53-binding protein 1 (53BP1) plays critical roles in DNA double strand break (DSB) repair by promoting non-homologous end joining (NHEJ), and loss of 53BP1 abolishes PARPi sensitivity in BRCA1-deficient cells by restoring homologous recombination (HR). 53BP1 is one of the proteins initially recruited to sites of DSBs via recognition of H4K20me2 through the Tudor-UDR domain and H2AK15ub through the UDR motif. Although extensive studies have been conducted, it remains unclear how the post-translational modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Just as JMJD2A and L3MBTL1 compete with 53BP1 for H4K20Me 2 binding, the E3 ubiquitin ligases RNF169 and RAD18 also compete with 53BP1 for binding to H2AK15ub (53,54). The ability of 53BP1 to bind to H2AK15ub is also limited by phosphorylation or acetylation of key residues within the ubiquitin-dependent recruitment region (13,55,56). In addition to its recruitment, the stability of 53BP1 is also regulated by proteasome-mediated degradation dependent on the E2 enzyme, UBCH7 (57).…”
Section: Brca1 and 53bp1: A Key Regulatory Partnershipmentioning
confidence: 99%
“…Just as JMJD2A and L3MBTL1 compete with 53BP1 for H4K20Me 2 binding, the E3 ubiquitin ligases RNF169 and RAD18 also compete with 53BP1 for binding to H2AK15ub (53,54). The ability of 53BP1 to bind to H2AK15ub is also limited by phosphorylation or acetylation of key residues within the ubiquitin-dependent recruitment region (13,55,56). In addition to its recruitment, the stability of 53BP1 is also regulated by proteasome-mediated degradation dependent on the E2 enzyme, UBCH7 (57).…”
Section: Brca1 and 53bp1: A Key Regulatory Partnershipmentioning
confidence: 99%
“…Thus, human premature aging disorders are strongly associated with defects in DSBR, BER, and NER . Furthermore, repair of DNA damage is an energy demanding process and it is becoming increasingly evident that DNA damage and persistent DDR‐linked cellular stress leads to mitochondrial dysfunction and metabolic defects . The following paragraphs discuss the molecular mechanisms underlying this signaling and how it relates to cellular bioenergetics/energy homeostasis and the cellular abundance of ATP and NAD + .…”
Section: Dna Damage Response Pathwaysmentioning
confidence: 99%
“…Thus, human premature aging disorders are strongly associated with defects in DSBR, BER, and NER [14]. Furthermore, repair of DNA damage is an energy demanding process [15][16][17][18][19][20] and it is becoming increasingly evident that DNA damage and persistent DDR-linked cellular stress leads to mitochondrial dysfunction and metabolic defects [21].…”
Section: Dna Damage Response Pathwaysmentioning
confidence: 99%
“…Increasing studies have revealed that acetylation within the domain region were capable of regulating the function of proteins (19,20). For instance, acetylation of K1626 and K1628 in the Tudor-UDR domain of 53BP1 was dynamic regulated by CBP and KDAC2, which was associated with 53BP1 interaction with nucleosomes and the choice of DNA repair pathway (21). Hence, via analyzing the regions of these acetylation sites on the 50 repair protein, 9 acetylated or deacetylated Kac sites were observed to locate in the function domains of 7 repair proteins.…”
Section: Discussionmentioning
confidence: 99%